Projeto e implementação em DSP de sistema de comunicação multiportadora baseado no padrão G.fast - ALMEIDA, Igor Mesquita de (Universidade Federal do Pará, 2014)
The evolving broadband access systems using copper networks are currently deployed in a frequency band that goes up to 30 MHz, as specified in VDSL2. As hybrid fiber-copper architectures become more important in the industry and academia, using shorter loop lengths (i.e. up to 250 meters) from the last distribution point to users enables adopting even higher frequencies to achieve very high data rates of 500 Mbps and beyond, as is the case with the G.fast standard under development by ITU-T. In this work, a time-domain simulator has been developed to evaluate G.fast system performance with different cyclic extension lengths and different reference loop topologies specified by ITU-T. The simulation results show that G.fast systems are robust to bridged taps and capable of providing very high data rates for all simulated loop topologies to support next generation ultra high speed broadband services. Furthermore, this work describes an ongoing effort to implement a G.fast-based modem protototype in a hybrid multicore DSP and FPGA environment using readily-available evaluation kits purchased by UFPA. Architecture plans, communication protocols and benchmarks are presented and evaluated to conclude that such a prototype is both feasible and flexible to support several avenues of research in next generation broadband.